2016
DOI: 10.1007/s10433-016-0381-4
|View full text |Cite
|
Sign up to set email alerts
|

Relations between views on ageing and perceived age discrimination: a domain-specific perspective

Abstract: This study investigates the relation between age stereotypes and perceived age discrimination. Existing evidence for such a relation is notoriously ambiguous with regard to its direction-age stereotypes can predict (perceived) discrimination, but experiencing discrimination may also change views on ageing-which is why we used a dataset with two waves to disentangle the direction of the associations. Considering research on the multi-dimensionality of views on ageing and perceived age discrimination, we address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 45 publications
1
32
0
Order By: Relevance
“…Considering the subjective nature of perceived age discrimination, we neither intend to deny that "objective" age discrimination exists nor do we consider (falsely) perceiving age discrimination to be less harmful than noticing actual age discrimination. This perspective can, however, help to identify individuals or situations for whom or which the probability of perceiving discrimination is particularly high (Voss et al 2017), and it also elucidates possible relations between (perceived) age discrimination and an actor's (as well as a perceiver's) behaviour. Although perceived and "objective" age discrimination are conceptually different, they are somehow empirically linked.…”
Section: Ageist Behaviour and Perceived Age Discriminationmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the subjective nature of perceived age discrimination, we neither intend to deny that "objective" age discrimination exists nor do we consider (falsely) perceiving age discrimination to be less harmful than noticing actual age discrimination. This perspective can, however, help to identify individuals or situations for whom or which the probability of perceiving discrimination is particularly high (Voss et al 2017), and it also elucidates possible relations between (perceived) age discrimination and an actor's (as well as a perceiver's) behaviour. Although perceived and "objective" age discrimination are conceptually different, they are somehow empirically linked.…”
Section: Ageist Behaviour and Perceived Age Discriminationmentioning
confidence: 99%
“…A process of mutual influence is conceivable whereby negative self-perceptions of ageing are related to more perceived age discrimination, which in turn reinforces negative self-perceptions of ageing. Therefore Voss et al (2017) examined the association among self-perceptions of ageing and perceived age discrimination across two measurement occasions that were separated by a three-year interval. Their results point to a stronger effect of self-perceptions of ageing on subsequent changes in perceived age discrimination.…”
Section: Review Of Existing Evidence For Age Stereotypes As Predictormentioning
confidence: 99%
See 1 more Smart Citation
“…This is important because self-directed ageism is a risk for increased morbidity and mortality (Levy et al 2002(Levy et al , 2009). In their paper, Voss et al (2016, in this section of EJA) examine a fundamental research question concerning the temporal relation between age stereotypes and perceived age discrimination. Much of the literature concerns the negative effects of age discrimination (Angus and Reeve 2006).…”
Section: Ageism At the Individual Levelmentioning
confidence: 99%
“…Hence, ones' perceptions of the situation as discriminatory or not are affected by one's own views on ageing. The authors concluded that holding negative views on ageing either predisposes individuals to categorize other people's behaviours as age discrimination or act as self-fulfilling prophecies to elicit ageist behaviours by others (Voss et al 2016).…”
Section: Ageism At the Individual Levelmentioning
confidence: 99%